(untitled) (Polis (Santiago), 2018)
The following lines expose the concept of operation as a specific type of collective action, that means an organized mobilization of resources bounded in target and times. In chilean ‘Falange Nacional’ it is possible to distinguish, between its early and late periods as organization, the way they function and produce effects, in at least two types of operations, one characterized as doctrinaire and the other as pragmatic . The main effects of the performance of these types, are located in the conception and action of the organic model of party and in the figure of partisan member associated with that model.